The Gender Wage Gap in the Human Capital Framework: A Cross-Nordic Assessment Based on PIAAC. Sooline palgalõhe täiskasvanute oskuste uuringu PIAAC tulemuste raamistikus: Eesti Põhjamaade võrdluses - Tverdostup, Maryna; Paas, Tiiu (Estonian Discussions on Economic Policy, 2016)
This paper studies the role of human capital in gender wage disparities. Despite increasing convergence of male and female human capital attainments, substantial differences remain. We focus on the human capital dimensions specific for a certain gender as additional drivers of the pay differential. Relying on PIAAC (the Program for the International Assessment of Adult Competencies) data, we incorporate both formal educational attainment and actual cognitive skills in the definition of human capital. The results showed that the association between higher skill and formal education is particularly low for Estonian men, whereas wage returns for these skills are remarkably high in Estonia, compared to other Nordic states. It suggests that factors other than formal education play a substantial role in human capital accumulation in the case of Estonian males but not so remarkable in the case of Nordic countries.